I am Once Again Asking for Your Attention: A Replication of Feature-Based Attention Modulations of Binding Effects with Picture Stimuli - Tarini Singh; Lars-Michael Schöpper; Christian Frings (Journal of Cognition)
Action control theories assume that stimulus and response features are integrated or bound into short term episodic traces. A repetition of any of these features results in a retrieval of the entire episodic trace, and can thus facilitate or interfere with future actions. Along with stimuli features, features of the response and any other irrelevant stimuli that are present, are also integrated into such traces and can influence future actions. Using word stimuli, Singh et al. (2018) observed that such so-called binding effects are larger for attended features relative to unattended features. This was the case even for features generally believed to be automatically processed, like valence. Since previous research has shown differences in the processing of word and picture stimuli, it is questionable whether the attentional modulations in the above study would extend to picture stimuli. In order to examine this question, Experiment 1 replicated the design of Singh et al. (2018) but used picture instead of word stimuli. In order to directly compare word and picture stimuli, the data of Singh et al (2018) were re-analysed together with the data of the present study. In Experiment 2, the alternative hypothesis, that the effects were driven by the encoding of stimulus contingencies, was tested. Taken together, the findings of the present study replicate those of Singh et al. (2018), indicating that even with picture stimuli, valence related binding effects are modulated by attention allocation.